Fantasy, desire and identity framing the identity construction of Luh Sekar - Eliyanah, Evi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2012)
This article examines the roles of fantasy and desire in the process of identity construction as experienced by Luh Sekar, one of the characters in Oka Rusmini’s most notable work of fiction, Tarian Bumi. Employing Stuart Hall’s postulate on identity construction in a critical reading of the novel, the study finds that the subject’s identity construction is highly influenced by her fantasy and desire related to caste and gender. Caste not only structures women’s social location through rank and role, but also, as part of the symbolic order, constitutes women themselves.